PENGARUH PENERAPAN SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN NAGEKEO - Sada, Rikhardus Kodhi; Made, Anwar; Dianawati, Eris (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2017)
This study aims to determine the effect of the Implementation of the Government Internal Control System on the Quality of the Financial Statements of the Regional Government of The Nagekeo Regency. This research uses a quantitative approach, using primary data through questionnaires. Respondents in this study are part of the financial management of 35 SKPD Nagekeo Regency. The variables are the Government Internal Control System as an independent variable and the Quality of Government Financial Statements as the dependent variable. Data analysis uses multiple regression statistical methods. Hypothesis test results indicate that the application of the government's internal control system has a positive and significant effect on the quality of the financial statements of the Nagekeo Regency government.